Networks, Start-Up Capital and Women's Entrepreneurial Performance in Africa: Evidence from Eswatini - Zuzana Brixiova; Thierry Kangoye (Institute of Labor Economics (IZA), 2019)
This paper analyzes the role of networks in access of women entrepreneurs to start-up capital and firm performance in Eswatini, a country with one of the highest female unemployment rates in Africa. The paper first shows that higher initial capital is associated with better sales performance for both men and women entrepreneurs. Women entrepreneurs start their firms with smaller start-up capital than men and are more likely to fund it from their own sources, which reduces the size of their firm and sales level. However, women with higher education start their firms with more capital than their less educated counterparts. Moreover, women who receive support from professional networks have higher initial capital, while those trained in financial literacy more often access external funding sources, including through their networks.
Keywords: L53; O12; 330; networks; start-up capital; multivariate analysis; Africa